2016
DOI: 10.1016/j.jot.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimising femoral-head osteochondral allograft transplantation in a preclinical model

Abstract: SummaryBackground/ObjectiveOsteochondral autografting and allografting of the femoral head have been described as treatments for avascular necrosis without segmental collapse, fracture, osteochondritis dissecans, and tumours. One long-term study reported that 80% of nonsteroid-treated patients had successful outcomes. Most data are compiled from small case reports or series. Although these results are encouraging, to the authors’ knowledge, there is no basic scientific evidence regarding optimal graft source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Many treatment options for cartilage damage are used in both human and canine medicine, including non-surgical management, osteochondral autografting, or synthetic resurfacing with focal, unicompartmental, or total joint replacement systems (8)(9)(10)(11)(12)(13)(14). However, osteochondral allograft (OCA) transplantation is a treatment option used in people, which has not been described for use in clinical canine patients (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many treatment options for cartilage damage are used in both human and canine medicine, including non-surgical management, osteochondral autografting, or synthetic resurfacing with focal, unicompartmental, or total joint replacement systems (8)(9)(10)(11)(12)(13)(14). However, osteochondral allograft (OCA) transplantation is a treatment option used in people, which has not been described for use in clinical canine patients (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Osteochondral allograft transplantation has been reported to be effective for resurfacing cartilage defects in the human knee, ankle, hip, shoulder, and elbow (17,18,(24)(25)(26). Resurfacing is most commonly performed using cylindrical OCA cores, or "plugs, " using essentially the same equipment and techniques used for osteochondral autograft transfer (OAT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a promising approach to regenerating a biological joint, but whether it can become a cost-effective approach that can replace osteochondral allograft transplantation—a well-accepted surgical treatment—remains for further investigation. The objective of Crist et al’s study presented in this issue of the journal was to compare femoral head osteochondral autografts and allografts in a canine model [13] . The authors reported that there was a significant loss in range of motion, chondrocyte viability and articular cartilage integrity 8 weeks after implantation of both small autografts and allografts, whereas chondrocytes in the large allografts maintained their viability and structural integrity throughout the study period.…”
Section: Materials or Allograft To Promote Tissue Regenerationmentioning
confidence: 99%
“…Lacking of blood supply and innervation, articular cartilage has a very limited capacity for self-healing once damaged [1], [2]. To treat the cartilage defects, early clinical intervention includes bone marrow stimulation techniques, cartilage plug transplant, and expanded autologous chondrocyte or mesenchymal stem cell implantation [2], [3], [4]. Given the limitations of current surgical approaches to treat articular cartilage lesions, tissue engineering has been pursued extensively in recent decades and exhibited promising applications in clinical treatment [5], [6], [7], [8].…”
Section: Introductionmentioning
confidence: 99%